أسباب نفث الدم خبرة مشفى الأسد الجامعي باللاذقية (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة لتقييم الأسباب المختلفة لنفث الدم، وتبيان قيمة الصورة الشعاعية البسيطة للصدرCXR  والتصوير الطبقي المحوري للصدر CT scan والتنظير القصبي الليفي المرن في تقييم هذه الأسباب. اشتملت الدراسة على (81) مريضاً (48 ذكراً و 33 أنثى), تراوحت أعمارهم بين (18-88)  سنة, من بينهم  (52) مريضاً مدخناً و (29) مريضاً غير مدخن. الأسباب الأساسية لنفث الدم كانت : توسع قصبي (19.8%), سرطان قصبي(18.5%), التهاب قصبات حاد(9.9%), ذات رئة(8.6%), , سل رئوي(7.4%), التهاب قصبات مزمن(6.7%). أظهرت الدراسة أن نفث الدم كان خفيفاً لدى(56.8%), معتدلاً لدى (29.6%) و غزيراً لدى (13.6%) من المرضى. نسبة إيجابية الاستقصاءات المجراة كانت على النحو الآتي: CXR (60.5%), CTscan (77.6%), تنظير القصبات الليفي المرن (67.3%), لكن عندما شاركنا الـ CT scan مع التنظير القصبي فإن نسبة الإيجابية وصلت إلى (86.5%). This study was performed to evaluate the relative frequency of the different causes of haemoptysis and the role of chest radiography, computed tomography (CT) scanning and fibrobronchoscopy to estimate them. This study included (81) patients (48 males and 33 females), ranging in age between (18-88) years, (52 smokers and 29 nonsmokers). The main causes of haemoptysis were: bronchectasis (19.8%), bronchogenic cancer (18.5%), acute bronchitis (9.9%), pneumonia (8.6%), tuberculosis (7.4%), and chronic bronchitis (6.7%).the haemoptysis was mild in (56.8%), moderate in (29.6%) and massive in (13.6%). The positivism of the diagnostic procedures was: CXR(60.5%), CT(77.6%), bronchoscopy (67.3%), but when combining a CT study together with a bronchoscopy, the positive yield notched (86.5%).